Common Susceptibility Loci for Male Breast Cancer. (12th August 2020) - Maguire, Sarah; Perraki, Eleni; Tomczyk, Katarzyna; Jones, Michael E; Fletcher, Olivia; Pugh, Matthew; Winter, Timothy; Thompson, Kyle; Cooke, Rosie; ,; Trainer, Alison; James, Paul; et al.
Abstract: Background: The etiology of male breast cancer (MBC) is poorly understood. In particular, the extent to which the genetic basis of MBC differs from female breast cancer (FBC) is unknown. A previous genome-wide association study of MBC identified 2 predisposition loci for the disease, both of which were also associated with risk of FBC. Methods: We performed genome-wide single nucleotide polymorphism genotyping of European ancestry MBC case subjects and controls in 3 stages. Associations between directly genotyped and imputed single nucleotide polymorphisms with MBC were assessed using fixed-effects meta-analysis of 1380 cases and 3620 controls. Replication genotyping of 810 cases and 1026 controls was used to validate variants with P values less than 1 × 10 –06 . Genetic correlation with FBC was evaluated using linkage disequilibrium score regression, by comprehensively examining the associations of published FBC risk loci with risk of MBC and by assessing associations between a FBC polygenic risk score and MBC. All statistical tests were 2-sided. Results: The genome-wide association study identified 3 novel MBC susceptibility loci that attained genome-wide statistical significance ( P < 5 × 10 –08 ). Genetic correlation analysis revealed a strong shared genetic basis with estrogen receptor–positive FBC. Men in the top quintile of genetic risk had a fourfold increased risk of breast cancer relative to those in the bottom quintile (odds ratio = 3.86, 95% confidence interval = 3.07 to 4.87, P = 2.08 × 10 –30 ). Conclusions: These findings advance our understanding of the genetic basis of MBC, providing support for an overlapping genetic etiology with FBC and identifying a fourfold high-risk group of susceptible men.